2021
DOI: 10.3390/biom11121907
|View full text |Cite
|
Sign up to set email alerts
|

Liver Regeneration and Cell Transplantation for End-Stage Liver Disease

Abstract: Liver transplantation is the only curative option for end-stage liver disease; however, the limitations of liver transplantation require further research into other alternatives. Considering that liver regeneration is prevalent in liver injury settings, regenerative medicine is suggested as a promising therapeutic strategy for end-stage liver disease. Upon the source of regenerating hepatocytes, liver regeneration could be divided into two categories: hepatocyte-driven liver regeneration (typical regeneration)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…The liver contains different cell types: parenchymal cells (<80% of liver mass), such as hepatocytes and non-parenchymal cells (20–40% of liver mass), which include liver sinusoidal endothelial cells (LSECs), biliary epithelial cells (BECs), Kupffer cells, and hepatic stellate cells, as well as various immune cells. Resection or acute injury of the liver induces a regenerative process that is mainly driven by hepatocytes, while in chronic liver diseases, hepatocyte progenitor cells are involved in regeneration [ 77 ]. Typically, liver regeneration comprises three phases: initiation, proliferation and termination.…”
Section: Inherent Liver Regenerationmentioning
confidence: 99%
“…The liver contains different cell types: parenchymal cells (<80% of liver mass), such as hepatocytes and non-parenchymal cells (20–40% of liver mass), which include liver sinusoidal endothelial cells (LSECs), biliary epithelial cells (BECs), Kupffer cells, and hepatic stellate cells, as well as various immune cells. Resection or acute injury of the liver induces a regenerative process that is mainly driven by hepatocytes, while in chronic liver diseases, hepatocyte progenitor cells are involved in regeneration [ 77 ]. Typically, liver regeneration comprises three phases: initiation, proliferation and termination.…”
Section: Inherent Liver Regenerationmentioning
confidence: 99%
“…Although some authors, based on animal studies, dispute the role of hepatic progenitor cells in liver regeneration, most studies suggest that they become important in severe liver injury, as occurs in AH[ 17 ]. Indeed, it has been demonstrated that the origin of hepatocytes during liver regeneration varies in different models, and that although hepatocytes are the main drivers for regeneration under normal conditions, an alternative regeneration process may be initiated by liver progenitor cells[ 46 ].…”
Section: Experimental Options Targeting Liver Regeneration For the Tr...mentioning
confidence: 99%
“…Non-hepatic progenitor cells represent a wide range of cells arising from different tissues. Mesenchymal SCs and hematopoietic SCs found in bone marrow represent the most frequently used SCs[ 46 ].…”
Section: Experimental Options Targeting Liver Regeneration For the Tr...mentioning
confidence: 99%
“…When people donate a part of their liver (or receive it), the liver tissue reaches ~80% of its original mass after six weeks, and the total recovery of the liver tissue takes about six months. This is accomplished by a typical liver regeneration mechanism that depends on pre-existing hepatocytes that replicate one day after PH [ 33 ]. After surgical resection, all the cell types of the liver are activated.…”
Section: Interdisciplinary Models Applied To Translational Medicinementioning
confidence: 99%
“…Proliferating hepatocytes produce growth factors and stimulate mitosis in other cell types. In humans, after the replication of different hepatic cells, a hypertrophic mechanism restores the liver volume [ 34 ], then the cytokines of the TGF-β superfamily, produced by hepatic stellate cells and Kupffer cells, control the termination phase indicating that proliferation should stop [ 33 , 34 ].…”
Section: Interdisciplinary Models Applied To Translational Medicinementioning
confidence: 99%